Outcomes associated with vaginectomy and vulvovaginectomy in 21 dogs. Issue 6 (9th June 2020) - Ogden, Jessica A.; Selmic, Laura E.; Liptak, Julius M.; Oblak, Michelle L.; Culp, William T. N.; de Mello Souza, Carlos H.; Grimes, Janet A.; Traverson, Marine; Cray, Megan; Abrams, Brittany E.; Wavreille, Vincent A.
Abstract: Objective: To report the outcomes of dogs with lesions of the genitourinary tract treated by vaginectomy or vulvovaginectomy. Study design: Multi‐institutional retrospective study. Animals: Female dogs that underwent vulvovaginectomy, complete vaginectomy, or subtotal vaginectomy from 2003 to 2018 with complete medical records and a minimum of 60 days follow‐up. Methods: Data collected from medical records included preoperative, intraoperative, and postoperative data, such as the occurrence of urinary incontinence (UIC), disease recurrence, and death/euthanasia. Results: This study included 21 dogs. Four dogs had vulvovaginectomy, six had complete vaginectomy, and 11 had a subtotal vaginectomy performed. The mean age at surgery was 9.2 years (SD, 3.3). Thirteen dogs were intact at presentation. Smooth muscle tumors were diagnosed most commonly (10 leiomyomata, three leiomyosarcomas, two leiomyofibromas). The median duration of follow‐up was 520 days (range, 71‐1955). Major complications requiring revision surgery were recorded in two dogs. Postoperative UIC occurred in six of 21 dogs, resolving spontaneously within 60 days in three dogs. Dogs with malignant tumors (n = 6) survived at least 71 days (median, 626; 95% CI, 71‐1245), and recurrence of disease occurred in two dogs. In dogs with benign tumors (n = 15), the median survival time was not reached. These dogs survived at least 104 days and had no recurrence of the disease. Conclusion: Vaginectomy and vulvovaginectomy resulted in prolonged survival and low rates of major complications and UIC. Clinical significance: This study provides evidence to recommend that the risks of this procedure and expectations should be discussed with clients.